2021
DOI: 10.1051/0004-6361/202040178
|View full text |Cite
|
Sign up to set email alerts
|

Blue extreme disk-runaway stars with Gaia EDR3

Abstract: Since the discovery of hypervelocity stars in 2005, it has been widely believed that only the disruption of a binary system by a supermassive black hole at the Galactic center (GC), that is, the so-called Hills mechanism, is capable of accelerating stars to beyond the Galactic escape velocity. In the meantime, however, driven by the Gaia space mission, there is mounting evidence that many of the most extreme high-velocity early-type stars at high Galactic latitudes do originate in the Galactic disk and not in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 55 publications
1
17
1
Order By: Relevance
“…Its orbit is indicative of interaction with Sag. A* (Koposov et al 2020;Irrgang et al 2021). Though the Hills mechanism does accelerate stars at low velocities as well, the stars in our sample are not compatible with the Hills mechanism.…”
Section: The Acceleration Mechanismcontrasting
confidence: 58%
See 1 more Smart Citation
“…Its orbit is indicative of interaction with Sag. A* (Koposov et al 2020;Irrgang et al 2021). Though the Hills mechanism does accelerate stars at low velocities as well, the stars in our sample are not compatible with the Hills mechanism.…”
Section: The Acceleration Mechanismcontrasting
confidence: 58%
“…Opportunities to discover and characterize HVSs have considerably increased since the initial discoveries, specially owing to the Gaia data releases. For example, Shen et al (2018) reported the discovery of three white dwarfs with velocities exceeding 1000 km s −1 , or the discovery of S5-HVS 1, an unbound A type star located at 9 kpc from the Sun travelling at a staggering 1700 km s −1 (Koposov et al 2020;Irrgang et al 2021). Bromley et al (2018), Marchetti et al (2018b,a), Boubert et al (2018), and Hattori et al (2018a) have all searched for HVSs candidates, with a focus on late-type stars, and found over 30 stars.…”
Section: Introductionmentioning
confidence: 99%
“…Opportunities to discover and characterize HVSs have considerably increased since the initial discoveries, especially owing to the Gaia data releases. For example, Shen et al (2018) reported the discovery of three white dwarfs with velocities exceeding 1000 km s −1 , and the discovery of S5-HVS 1, an unbound A-type star located at 9 kpc from the Sun and traveling at a staggering 1700 km s −1 (Koposov et al 2020;Irrgang et al 2021). Bromley et al (2018), Marchetti et al (2018aMarchetti et al ( , 2018b, Boubert et al (2018), and Hattori et al (2018a) have all searched for HVS candidates, with a focus on late-type stars, and found over 30.…”
Section: Introductionmentioning
confidence: 99%
“…With the notable exception of HVS candidate S5-HVS1 (Koposov et al 2020), it is notoriously difficult to indisputably associate known HVS candidates with an origin in the GC. For many candidates, tracing their trajectories backwards in time leads to a wide range of possible ejection locations (see Irrgang et al 2019;Kreuzer et al 2020;Irrgang et al 2021) due to their imprecise astrometry and large helicentric distances. Additionally, it is well-known that the GC is not the only potential birthplace of extreme-velocity stars.…”
Section: Data Availabilitymentioning
confidence: 99%